The role of polyamine metabolism in remodeling immune responses and blocking therapy within the tumor immune microenvironment - Lian, Jiachun; Liang, Yanfang; Zhang, Hailiang; Lan, Minsheng; Ye, Ziyu; Lin, Bihua; Qiu, Xianxiu; Zeng, Jincheng (Frontiers in Immunology, 2022)
The study of metabolism provides important information for understanding the biological basis of cancer cells and the defects of cancer treatment. Disorders of polyamine metabolism is a common metabolic change in cancer. With the deepening of understanding of polyamine metabolism, including molecular functions and changes in cancer, polyamine metabolism as a new anti-cancer strategy has become the focus of attention. There are many kinds of polyamine biosynthesis inhibitors and transport inhibitors, but not many drugs have been put into clinical application. Recent evidence shows that polyamine metabolism plays essential roles in remodeling the tumor immune microenvironment (TIME), particularly treatment of DFMO, inhibitor of ODC, a key enzyme of polyamine metabolism, alters the immune cell population in the tumor microenvironment. Tumor immunosuppression is a major problem in cancer treatment. More and more studies have shown that the immunosuppressive effect of polyamines can help cancer cells to evade immune surveillance and promote tumor development and progression. Therefore, targeting polyamine metabolic pathways is expected to become a new avenue for immunotherapy for cancer.